2019
DOI: 10.5294/laclil.2019.12.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Promoting Teacher Reflection: A Review Article

Abstract: The present review article is intended to bring the significant issue of teachers’ reflective practice into the limelight by overviewing how this concept evolved through time and what it promises for successful teaching. The concept of teacher reflection, defined as teachers’ beliefs about their teaching practice, has been subjected to a number of criticisms regarding its instrumental nature, disregard of social justice, and a vague reinforcement of the existing ideologies instead of challenging beliefs. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Further, reflective thinking practice gives the teacher a vision to see how their beliefs on pedagogical decisions they decide influences the teaching process. In a specific context, reflective teaching provides a big chance to promote teachers' lifelong learning, give more opportunities to do self-assessment, increase self-belief, and strengthen teaching awareness (Choy & Oo, 2012;Moayeri & Rahimiy, 2019). This will be useful for the development of teacher competence and professionalism in creating qualified learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Further, reflective thinking practice gives the teacher a vision to see how their beliefs on pedagogical decisions they decide influences the teaching process. In a specific context, reflective teaching provides a big chance to promote teachers' lifelong learning, give more opportunities to do self-assessment, increase self-belief, and strengthen teaching awareness (Choy & Oo, 2012;Moayeri & Rahimiy, 2019). This will be useful for the development of teacher competence and professionalism in creating qualified learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the reflective process, teachers are encouraged not only to describe but also examine and challenge embedded assumptions at each level, so that they can use the framework as a lens through which they can view their professional (and even personal) worlds, and what has shaped their professional lives as they become more aware of their philosophy, principles, theories, practices and how these impact issues inside and beyond practice. With regards to reflective teaching, teachers need to get involved in an evidence-based reflective practice that empowers them to express to themselves (and others) what they do, how they do it, why they do it, and, lastly, how their teaching influences learners' achievement (Moayeri & Rahimiy, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The preliminary results revealed that additional modifications to the strategy were needed along with experimenting with other LMS or digital platforms, as well as the design of additional tools and interaction patterns that would further foster autonomy amongst learners at university language centers. On another note, Moayeri and Rahimiy (2019) provide a systematic literature review on teacher reflection, in which key insights as to the development of evolution of teacher reflection.…”
Section: In This Issuementioning
confidence: 99%